2017
DOI: 10.1002/jsfa.8444
|View full text |Cite
|
Sign up to set email alerts
|

Changes in monosaccharides, organic acids and amino acids during Cabernet Sauvignon wine ageing based on a simultaneous analysis using gas chromatography–mass spectrometry

Abstract: BACKGROUND: Monosaccharides, organic acids and amino acids are the important flavour-related components in wines. The aim of this article is to develop and validate a method that could simultaneously analyse these compounds in wine based on silylation derivatisation and gas chromatography-mass spectrometry (GC-MS), and apply this method to the investigation of the changes of these compounds and speculate upon their related influences on Cabernet Sauvignon wine flavour during wine ageing. This work presented a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…We found that succinic acid, lactic acid, fumaric acid, and glycolic acid represented the distinguishable SDMs in KL Xiaoqu. Succinic acid, a main product of the TCA cycle, is known as the "wine skeleton" (Zhang et al, 2017) and, when combined with lactic acid, provides the unique sourness and umami taste to the final product. Additionally, lactic acid is the central precursor of ethyl lactate, which is the key flavoring component in liquor (Cai et al, 2019;Liu and Miao, 2020).…”
Section: Analyses Of Non-volatile Metabolitesmentioning
confidence: 99%
“…We found that succinic acid, lactic acid, fumaric acid, and glycolic acid represented the distinguishable SDMs in KL Xiaoqu. Succinic acid, a main product of the TCA cycle, is known as the "wine skeleton" (Zhang et al, 2017) and, when combined with lactic acid, provides the unique sourness and umami taste to the final product. Additionally, lactic acid is the central precursor of ethyl lactate, which is the key flavoring component in liquor (Cai et al, 2019;Liu and Miao, 2020).…”
Section: Analyses Of Non-volatile Metabolitesmentioning
confidence: 99%
“…The content of glutamine increased rapidly after 4 days of fermentation but decreased after 6 days, which might be particularly related to the consumption of nitrogen at the end of the fermentation. According to the reported, the main reason for the decrease in amino acid content is the Strecker reaction (Zhang et al, 2017).…”
Section: Differential Metabolite Analysismentioning
confidence: 99%
“…Organic acids such as citric acid, L-malic acid, and succinic acid are products of the TCA cycle, playing an essential role in the flavor formation of wine, and are called "wine skeletons" (Zhang et al, 2017). Duringd fermentation, glucose is subjected to hexokinase in the glycolytic pathway to produce G6P, subsequently producing F6P under the action of isomerase.…”
Section: F I G U R Ementioning
confidence: 99%
“…[21] Organic acids are called "wine skeletons" due to their contribution to flavor and taste. [43] The organic acid in the wine can originate from raw materials and/or microbial metabolism. Seo et al (2016) [21] suggested that the key organic acids (lactic, malic, and succinic acids) in Makgeolli are primarily produced by yeast metabolism.…”
Section: Identification Of Significantly Different Metabolitesmentioning
confidence: 99%